Analysis of Students’ Errors in Solving Mathematical Proof Problems on Real Numbers - Rahma Ramadhani; Iftitaahul Mufarrihah; Nihayatus Sa’adah (Pi: Mathematics Education Journal, 2026)
The aim of this study is to analyze students’ errors in solving mathematical proof problems on real numbers using Kastolan’s Theory. This study used a qualitative descriptive approach with third-semester students, who have taken the Real Analysis course, as the subjects. Data was collected through validated written tests consisting of three proof questions and interviews. Data analysis used the Miles and Huberman model with criterion sampling for subject selection. The results of the study showed three types of errors, namely conceptual, procedural, and technical errors. The conceptual errors found were errors in using definitions and errors in using arguments caused by a lack of understanding of deductive proofs. The procedural errors found were errors in writing systematic steps and errors caused by answers that did not return to the conclusion due to difficulties in constructing arguments systematically. Meanwhile, the technical errors found were errors in writing notation and errors in copying simple expressions due to carelessness. The most dominant errors were technical errors, especially in writing mathematical notation or symbols and copying or simplifying expressions. Further research is recommended to develop and test effective learning strategies or models to minimise conceptual, procedural, and technical errors.